2014
DOI: 10.1111/cch.12215
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the parenting style of foster parents on the behaviour problems of foster children

Abstract: This highlights the key role that foster carers play in terms of tackling the behaviour problems that foster children present. The findings also suggest that preparation for fostering should focus especially on ways of helping foster parents both to acquire positive parenting strategies and to avoid authoritarian and permissive parenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
0
31
0
2
Order By: Relevance
“…Foster parents can share ideas with each other about how to work with a child who are picky eaters or how to handle chores. Foster parents may need additional help in developing and maintaining social support networks (Fuentes, Salas, Bernedo, & García‐Martín, ; Harden, Clyman, Kriebel, & Lyons, ) and have requested more time with experienced peers or “veteran” foster parents (Cooley & Petren, ).…”
Section: Discussionmentioning
confidence: 99%
“…Foster parents can share ideas with each other about how to work with a child who are picky eaters or how to handle chores. Foster parents may need additional help in developing and maintaining social support networks (Fuentes, Salas, Bernedo, & García‐Martín, ; Harden, Clyman, Kriebel, & Lyons, ) and have requested more time with experienced peers or “veteran” foster parents (Cooley & Petren, ).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, Holland (2009) found that children who are placed in foster care and then age out without adoption or reunification with the birth family demonstrated worse outcomes than those who were in situations of maltreatment, but remained with their biological family, suggesting a complicated calculus of factors that influence these outcomes. A child's personal characteristics and history of maltreatment, especially sexual abuse, mediates placement disruption (Crum, 2009), yet Fuentes et al (2014) found that traits like age, race/ethnicity, and length of placement were not significant predictors of displacement.…”
Section: Foster Youth and Foster Familiesmentioning
confidence: 99%
“…Children often enter foster care having suffered emotional, psychological, and/or physical maltreatment along with learned maladaptive coping skills, all while experiencing disruption and loss. This combination of factors often leads to negative outcomes for youth (e.g., Bigner, 2010;Ahmed, Windsor, & Scott, 2015;Fuentes, Salas, Bernedo, & Garcia-Martin 2014). However, many young people who move through the foster care system experience positive outcomes and healthy development; this is especially true for those who leave dangerous situations, are placed with proactive, well-trained foster caregivers, and receive support from the wider community.…”
Section: Introductionmentioning
confidence: 99%
“…Parents play an important role in establishing and maintaining children's oral health behaviours through their beliefs 26 , role modelling 27 , parenting self-efficacy 28 and parenting style 29 , yet few studies have explored foster carers' parenting styles or examined the foster care environment in the context of children's health 30 . Lipscombe et al 31 suggested that an authorative parenting style that involved explaining rules and behaviours and setting boundaries was the style that foster children were most able to adapt to.…”
Section: Introductionmentioning
confidence: 99%